Diversity of Macrofungi in the Western Ghats of Karnataka (India) - Usha, N.; Janardhana, G. R. (Indian Forester, 2014)
The present investigation was carried out in the forests of five districts of western ghats of Karnataka which includes B.R. Hills of Chamarajnagar, H.D. Kote forest of Mysore, Aanekaadu forest of Kodagu, Bisle forest of Hassan and forests of Chickmagalur districts representing four different habitats such as grass, litter, wood and soil respectively. The fruiting bodies of macrofungi were collected between August 2010 and August 2012. In an extensive survey a total of 135 species of macrofungi belonging to 56 genera and 34 families were enumerated. Association of species was found to be abundant with litter followed by wood, grass and soil respectively Members of the family Agaricaceae were found to be predominant followed by Polyporaceae, Marasmiaceae, Mycenaceae and Russulaceae. Species of macrofuring belonging to 18 other families were also recorded.